Karakteristik Kimia Biomassa untuk Energi (Chemical Characteristics of Biomass for Energy) - Deded S Nawawi; Anne Carolina; Tasya Saskia; Deni Darmawan; Siti L Gusvina (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
The chemical components of biomass were composed mainly by three elements, i.e. carbon, hydrogen, and oxygen. These elements composition may contribute to proximate properties and calorific value of biomass. Characterization of wood, wood bark, and bamboos biomass and its relation to biomass quality for energy were carried out based on their chemical components contents. The analyses of chemical components of biomass were performed according to Technical Association of Pulp and Paper Industry (TAPPI) standard and proximate analysis was carried out according to American Society for Testing and Materials (ASTM) standard. The characteristics of biomass for energy could be evaluated based on its chemical components; especially by cellulose/lignin ratio (C/L) and hemicellulose/lignin ratio (H/L). Generally, appropriate quality of lignocellulose biomass for energy tend to exhibit low C/L and H/L ratios, that is due to obtain low volatile content and high calorific value. Lignin seems to be the most responsible chemical component for high calorific value of biomass. The classification of biomass based on the chemical components ratios would be applicable for biomass with less heterogeneity in ash content and in the quite similar extractives content.